An Analysis of Traffic Congestion Due to Railway Crossings on Prof. Dr. Latumenten Road, Grogol, West Jakarta - Wisnu Akbar; Alizar Alizar (International Journal Multidisciplinary Science, 2025)
This study aims to analyze the impact of railway crossings on congestion levels, traffic volume, delays on Jalan Prof. Dr. Latumenten Grogol, West Jakarta. The research methods used include collecting traffic data through primary data from direct surveys and analyzing secondary data from related agencies. The parameters analyzed include vehicle volume, queue duration, side barrier performance, delays and frequency of crossing barrier closures. The method used refers to the Indonesian Road Capacity Guidelines (PKJI 2023). The final result of the research writing is to provide recommendations for handling traffic congestion due to railway crossings, such as proposals for the construction of flyovers or underpasses, improving traffic management in affected areas